Pembuatan Sabun Cuci Piring dengan memanfaatkan Jeruk Nipis (Citrus Aurantifolia s.) kepada Ibu-ibu PKK di Kampung Rantau Bertuah - Benny Heltonika; Nadia Jayanti Br Situmorang; Seffi Wulandari; Lisa; Siti Rolijjah; Rahmandani; Bahagia Nasution; Ahmad Farki; Choififah Nanda Khairani; Niken Septria Ningrum (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2023)
The use of dish soap is certainly very effective for cleaning our kitchen utensils. The problem that often occurs with dish soap is the presence of irritant contact dermatitis which is a cytotoxic effect on the skin, due to exposure to chemicals in soap. So one of the solutions to reduce it is the use of natural ingredients, one of which is lime, because it can give a soft impression, has bacterial activity, and moisturizes the skin. Community service activities carried out in Rantau Bertuah Village, Minas District, Siak Regency, Riau Province, one of the villages with great potential for lime plants. The purpose of this activity is to teach about making liquid dish soap by utilizing natural ingredients of lime. In addition, it is also expected to encourage the motivation of potential UMKM to PKK women in Kampung Rantau Bertuah, so that they can improve the family economy. The stages of activities carried out in this service program include the socialization stage, the demonstration stage of making dish soap, and the discussion stage. The number of participants who participated in the socialization activities were 15 PKK women. The results of the service showed that the people of Kampung Rantau Bertuah were very enthusiastic and responded positively to the socialization of making laundry soap